Forgiving and forgetting: Family Conflict Resolution through Customary Law among the Tolaki People of Southeast Sulawesi, Indonesia - Erens Elvianus Koodoh; Idaman Idaman; Danial Danial (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2024)
Introduction: Southeast Sulawesi's Tolaki people have a system of customary law that is infused with local knowledge and values. In addition to governing day-to-day activities, Tolaki customary law offers advice on how to settle disputes, particularly those inside the family. In reality, Tolaki customary law places a strong emphasis on the idea of forgetting and forgiving as the primary method of resolving disputes. The phrase